QIYĀS SEBAGAI SEBUAH METODE DALAM NAHWU - Umi Nurun Ni’mah (Adabiyyāt: Jurnal Bahasa dan Sastra, 2008)
Language is an inseparable reality in human culture. It develops as the human civilization does. According to the linguists, classical Arabic has at least five methods of language development. Those are (a) isytiqāq (derivasi), (b) majāz (alegori), (c) naht (abrivasi), (d) ta’rīb (loan) dan (e) qiyās. Qiyas is exclusively analyzed in this research because it is the most common method, which is used widely by the linguists through its al-simā’ stage. This paper finds the fact that qiyas method in Arabic linguistic traditions have evolved into the pre and post al Khalîl bin Ahmad al-Farāhidī period.